A longitudinal study on the high involvement work system and its effect on job resources, job demands and outcomes among New Zealand employees : considerate leadership as a moderator : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science (Psychology), Massey University, Albany, New Zealand - Raley, Tabitha (Massey University, 2024)
Retaining a high-quality workforce is synonymous with organisational excellence. New Zealand (NZ) currently experiences a large fluctuation of its high-quality workforce moving in and out of the country (OECD, 2024). The issue we are faced with is an influx of competition and fewer high-quality employees. New Zealand (NZ) organisations are therefore tasked with producing and maintaining a work system that attracts, develops, and retains high-quality employees. In the study, we turn to employees’ involvement to achieve a high-quality workforce. While several important factors contribute to the quality of a workforce, we must begin by recognising an individual’s quality of life (QoL) as an essential element. The quality of an individual’s life will likely predict the quality of work (QoW) one produces (Bubonya et al., 2017; Lim et al., 2000). Using a sample of 250 New Zealand (NZ) employees, the longitudinal study systematically examined the effect of job resources, namely, opportunities for skill development, and emotional job demands on employees’ quality of work (QoW) and quality of life (QoL), while highlighting mediating effects of these variables on the relationship between employee involvement and employee outcomes. The analysis of our quantitative data indicated the significant positive effect of opportunities for skill development on employees’ quality of work (QoW) and quality of life (QoL). In addition, the high involvement work system (HIWS), conceptualised by the PIRK model’s four dimensions (power, information sharing, rewards and knowledge), had significant and positive effects on opportunities for skill development. Moreover, information sharing produced a significant and negative effect on emotional job demands. Emotional job demands mediated the relationships between the high involvement work system (HIWS) and employees’ quality of work (QoW) and quality of life (QoL). Opportunities for skill development produced a mediating effect on the relationship between the high involvement work system (HIWS) and only employees’ quality of work (QoW). A considerate leadership style produced no moderating effects on the high involvement work system (HIWS) and employee’s quality of work (QoW) and quality of life (QoL) but did directly effect employees’ opportunities for skill development. This study contributes to the limited longitudinal research in New Zealand (NZ) and provides empirical evidence on organisational-level change that supports employee outcomes, thus helping to progress employees’ involvement in New Zealand (NZ) organisations.
Keywords: 520104 Industrial and organisational psychology (incl. human factors)